Fonocardiógrafo com tecnologia móvel - Silva, Gisllaine Celina da (2016)
Cardiac auscultation is a technique widely used for state diagnosis of heart valves, helping to identify possible pathologies, but it has some limitations and because of this it has been used in conjunction with other techniques such as phonocardiogram and electrocardiogram. The phonocardiograph performs the monitoring of cardiac sounds, allowing the visualization of signals, and making possible to have a more precise diagnosis of the state of the heart valves. This project aims to develop a device that performs the acquisition and monitoring of cardiac signals. It was necessary to develop a circuit comprising a module for acquisition and conditioning of the signal, a control module, a communication module and the application to enable the visualization of cardiac signals. The signal acquisition is performed using an electret microphone followed by a filtration state, formed by a low-pass filter and high-pass to remove noise and to limit the frequency range of interest. Then the signal is amplified and then passes through an adder and inverter circuit, which aims to add an offset to the signal and cause it to be in the range of 0 to 5V, so it can be digitally processed the same way in ATMEGA328P. The microcontroller has two digital filters and signal encoding implemented, sending data to the Bluetooth module HC-05, which performs the communication between the microcontroller and application. The application was developed in the Android Studio software, using Java programming language. Simulations and tests were performed in all stages of development of the prototype. The results were satisfactory and meet what was expected. However, it was not possible to use the sampling frequency required to cover the full spectrum of heart sounds, which is restricted due to the real time exhibition of the graph, despite of that the frequency range used allows the identification of the first and second heart sound. The hardware worked properly and the cardiac signal displayed on the cell is similar to those found in the literature, being within the expected range and frequency.